'100 Is Not Much To You': Open Science and neglected accessibilities for scientific research in Africa. Issue 1 (1st January 2017) - Bezuidenhout, Louise; Kelly, Ann H.; Leonelli, Sabina; Rappert, Brian
Abstract: The Open Science (OS) movement promises nothing less than a revolution in the availability of scientific knowledge around the globe. By removing barriers to online data and encouraging publication in Open Access formats and Open Data archives, OS seeks to expand the role, reach and value of research. The promises of OS imply a set of expectations about what different publics hope to gain from research, how accountability and participation can be enhanced, and what makes science public in the first place. This paper presents empirical material from fieldwork undertaken in (bio)chemistry laboratories in Kenya and South Africa to examine the extent to which these ideals can be realized in a sub-Saharan context. To analyse the challenges African researchers face in making use of freely available data, we draw from Amartya Sen's Capabilities Approach. His theorisations of 'conversion factors' helps to understand how seemingly minor economic and social contingencies can hamper the production and (re-)use of online data. In contrast to initiatives that seek to make more data available, we suggest the need to facilitate a more egalitarian engagement with online data resources.